2012
DOI: 10.1016/j.jacc.2012.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Benefit With Prasugrel in the TRITON–TIMI 38 Coronary Artery Bypass Grafting Cohort

Abstract: Objectives The objective of this study is to characterize the bleeding, transfusion and other outcomes of patients related to the timing of prasugrel or clopidogrel withdrawal prior to coronary artery bypass grafting (CABG). Background There is little evidence to guide clinical decision making regarding the use of prasugrel in patients who may need urgent or emergency CABG. Experience with performing CABG in the presence of clopidogrel has raised concern about perioperative bleeding complications that are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 26 publications
2
141
0
10
Order By: Relevance
“…Now-a-days off-pump CABG surgery for multi vessel myocardial revascularization in high risk patients has been appeared to decrease the frequency of perioperative morbidity and mortalityand the duration of hospital stay 7, 9 . In a study, Smith et al observed that majority of patients are belongs to 61 to 70-year age group, which is similar to our study 8 .Islamoglu et al shows that total myocardial revascularization improves LV function postoperatively 10 .The low occurrence of readmission to the intensive care unit (ICU), come back to theater for bleeding or cardiac tamponade, infection, and stroke in these highrisk patients in our OPCABG series with concurrent CE contrasts positively with published OPCABG articles 11 . Inadequate myocardial revascularization has been appeared to be a standout amongst the most critical components that influences perioperative outcome, ventricular function, early and late mortality 12, 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Now-a-days off-pump CABG surgery for multi vessel myocardial revascularization in high risk patients has been appeared to decrease the frequency of perioperative morbidity and mortalityand the duration of hospital stay 7, 9 . In a study, Smith et al observed that majority of patients are belongs to 61 to 70-year age group, which is similar to our study 8 .Islamoglu et al shows that total myocardial revascularization improves LV function postoperatively 10 .The low occurrence of readmission to the intensive care unit (ICU), come back to theater for bleeding or cardiac tamponade, infection, and stroke in these highrisk patients in our OPCABG series with concurrent CE contrasts positively with published OPCABG articles 11 . Inadequate myocardial revascularization has been appeared to be a standout amongst the most critical components that influences perioperative outcome, ventricular function, early and late mortality 12, 13 .…”
Section: Discussionsupporting
confidence: 92%
“…In the 2015 ESC guidelines [36], prasugrel and ticagrelor have class I recommendations for the treatment of ACS and there is a class II indication for the recently approved cangrelor. Based on the TRITON-TIMI 38 [60,61] and PLATO [62] trials, the guidelines recommend a 12-month DAPT with new DES. In selected cases the duration of DAPT could be longer than 12 months, for clopidogrel or prasugrel up to 30 months [60][61][62][63][64], for ticagrelor up to 48 months [61,62,65].…”
Section: Third-generation P 2 Y 12 Antagonistsmentioning
confidence: 99%
“…Based on the TRITON-TIMI 38 [60,61] and PLATO [62] trials, the guidelines recommend a 12-month DAPT with new DES. In selected cases the duration of DAPT could be longer than 12 months, for clopidogrel or prasugrel up to 30 months [60][61][62][63][64], for ticagrelor up to 48 months [61,62,65]. However, because of observed bleeding complications it is recommend not using prasugrel prior to PCI-SI [60][61][62][63][64].…”
Section: Third-generation P 2 Y 12 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes not only patients who have undergone stent implantation, but also those with an acute coronary syndrome (ACS) who are medically treated, in whom the clustering of adverse thrombotic events has been described in the early period after interruption of oral antiplatelet agents. [10][11][12] The risk of a recurrent ischemic event for patients discontinuing or not adhering to aspirin treatment has been suggested to increase 3-fold, with similar estimates of risk in patients with an ACS, on secondary prevention for CAD and those undergoing coronary artery bypass grafting (CABG), and higher risk in patients treated with DESs. 13 Importantly, stent thrombosis is a serious complication that is known to commonly present with death or a large nonfatal myocardial infarction, usually with ST elevation.…”
Section: Ischemic and Bleeding Risk In Cad Patients Requiring Surgerymentioning
confidence: 99%